MEMORIAL William Joseph Vatter (1905-1990). - Moonitz, Maurice (The Accounting Review, 1991)
Presents an obituary for William Joseph Vatter, a distinguished member of the American Institute of the American Institute of Certified Public Accountants. Childhood; Career beginnings; Contribution to the accounting profession; Published works on managerial accounting; Personal character.